2008
DOI: 10.1002/pssb.200880262
|View full text |Cite
|
Sign up to set email alerts
|

Low positive thermal expansion in HfMgMo3O12

Abstract: In the search for materials with negative thermal expansion, the HfMgMo3O12 phase has been synthesized and characterized for the first time. It is established that this phase belongs to a new class of ceramics with the general formula A4+B2+M6+3O12 that crystallizes in orthorhombic symmetry of space group Pnma (62) or Pna21 (33). No evidence is observed for any phase transition of orthorhombic HfMgMo3O12 through differential scanning calorimetry and high‐temperature X‐ray diffraction measurements in the invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 21 publications
1
27
0
1
Order By: Relevance
“…The influence of the co-incorporation on the structures, phase transitions, and thermal expansion properties was studied by XRD, Raman spectroscopy, DSC, and dilatometry. We found that the monoclinic-to-orthorhombic phase transition temperature of the Fe 2 Mo 3 O 12 could be reduced effectively by the substitutional co-incorporation of Zr 41 and Mg 21 . As a result, Fe 0.4 (ZrMg) 0.8 Mo 3 O 12 crystallized already in orthorhombic phase at RT and could keep this structure as low as 103 K. Besides, the coincorporation also tailored the CTEs of the compound and the near-zero CTEs were obtained for the compound around x 5 1.7 (Fe 0.3 (ZrMg) 0.85 Mo 3 O 12 ).…”
Section: B Thermal Expansion Propertiesmentioning
confidence: 97%
“…The influence of the co-incorporation on the structures, phase transitions, and thermal expansion properties was studied by XRD, Raman spectroscopy, DSC, and dilatometry. We found that the monoclinic-to-orthorhombic phase transition temperature of the Fe 2 Mo 3 O 12 could be reduced effectively by the substitutional co-incorporation of Zr 41 and Mg 21 . As a result, Fe 0.4 (ZrMg) 0.8 Mo 3 O 12 crystallized already in orthorhombic phase at RT and could keep this structure as low as 103 K. Besides, the coincorporation also tailored the CTEs of the compound and the near-zero CTEs were obtained for the compound around x 5 1.7 (Fe 0.3 (ZrMg) 0.85 Mo 3 O 12 ).…”
Section: B Thermal Expansion Propertiesmentioning
confidence: 97%
“…However, it was not possible to grow single crystals of ZrMgMo 3 O 12 . Furthermore, although the powder diffraction approach can, in principle, resolve unknown crystal structures ab initio, powder diffraction experiments using synchrotron X-ray 24 and neutron 28 sources were unable to delineate the crystal structures, or even the space groups, of the related phases HfMgMo 3 O 12 and HfMgW 3 O 12 . Therefore, we have taken an alternate structuredetermination approach.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…26,27 AMgM 3 O 12 materials display low-magnitude thermal expansion in an orthorhombic space group, which had previously been determined through indexing analysis to be either Pna2 1 or Pnma. 24 26 The absence of structural information has precluded understanding of the mechanisms of thermal expansion in these materials, especially regarding the origins of low-magnitude thermal expansion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent years, a number of novel NTE materials have been designed based on the basic structure of A 2 M 3 O 12 family, including those with a general formula ABM 3 O 12 where A is tetravalent Hf 4+ or Zr 4+ and B is bivalent cation Mg 2+ or Mn 2+ , and M is W or Mo or a combination of them (Suzuki and Omote, 2004; Baiz et al, 2008; Gindhart et al, 2008; Marinkovic et al, 2008; Song et al, 2013; Li et al, 2014, 2016, 2017; Ge et al, 2016a; Liu et al, 2018) and those with a formula ABM 2 XO 12 where A and M are the same as in ABM 3 O 12 , B is a trivalent cation and X is P 5+ or V 5+ (Chen et al, 2016; Cheng et al, 2016b, 2017; Ge et al, 2016b,c). The most distinct characteristics of the materials with formula ABM 2 XO 12 are that they exhibit NTE over a wide temperature range and intense photoluminescence in the visible range.…”
Section: Introductionmentioning
confidence: 99%